Diversity of helicobacter pylori vacA and cagA genes and relationship to VacA and CagA protein expression, cytotoxin production, and associated diseases - Rudi, Jochen; Kolb, Christof; Maiwald, Matthias; Kuck, Dirk; Sieg, Andreas; Galle, Peter R.; Stremmel, Wolfgang (Journal of clinical microbiology, 1998)
The vacuolating cytotoxin and the cytotoxin-associated protein, encoded by vacA and cagA, respectively, are important virulence determinants of Helicobacter pylori. Sixty-five H. pylori strains were isolated from dyspeptic patients (19 with peptic ulcer disease, 43 with chronic gastritis, and 3 with gastric cancer) and studied for differences in the vacA and cagA genes and their relationship to VacA and CagA expression, cytotoxin activity, and the clinical outcome of infection. By PCR, fifty-four (83.1%) of 65 strains had the vacA signal sequence genotype s1 and only 10 (15.4%) had the type s2. After primer modification, the vacA middle-region types m1 and m2 were detected in 24 (36.9%) and 41 (63.1%) strains, respectively. The combinations s1-m2 (31 [47.7%]) and s1-m1 (23 [35.4%]) occurred more frequently than s2-m2 (10 [15.4%]) (P = 0.01). No strain with the combination s2-m1 was found. All 19 patients with peptic ulcers harbored type s1 strains, in contrast to 32 (74.4%) of 43 patients with gastritis (P = 0.02). The vacA genotype s1 was associated with the presence of cagA (P < 0.0001), VacA expression (P < 0.0001), and cytotoxin activity (P = 0.003). The cagA gene was detectable in 48 (73.8%) of 65 isolates and present in 16 (84.2%) of 19 ulcer patients and 29 (67.4%) of 43 patients with gastritis (P = 0.17). The vacA genotypes of German H. pylori isolates are identical to those previously reported. H. pylori strains of vacA type s1 are associated with the occurrence of peptic ulceration and the presence of cagA, cytotoxin activity, and VacA expression.